2018
DOI: 10.1186/s12879-018-3337-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and genomic characterization of community-acquired Clostridium difficile infections

Abstract: BackgroundClostridium difficile infection (CDI) is a major cause of morbidity and mortality in North America and Europe. The aim of this study was to identify epidemiologically-confirmed cases of community-acquired (CA)-CDI in a large North American urban center and analyze isolates using multiple genetic and phenotypic methods.MethodsSeventy-eight patients testing positive for C. difficile from outpatient clinics were further investigated by telephone questionnaire. CA-CDI isolates were characterized by antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…These patients must not have been discharged from a health-care facility in the previous 12 weeks. HA-CDI cases were defined as a patient with the onset of CDI symptoms that occurred more than 48 h after admission or less than 4 weeks after discharge from a health care facility or hospital [23]. The following clinical details were recorded for all subjects: patient demographics; antibiotic and medication history; laboratory data; and underlying health conditions.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…These patients must not have been discharged from a health-care facility in the previous 12 weeks. HA-CDI cases were defined as a patient with the onset of CDI symptoms that occurred more than 48 h after admission or less than 4 weeks after discharge from a health care facility or hospital [23]. The following clinical details were recorded for all subjects: patient demographics; antibiotic and medication history; laboratory data; and underlying health conditions.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Administration of antibiotics is the primary risk factor for the development of C . difficile infection (CDI) [1, 6, 7]. However, patients can develop CDI outside of a healthcare facility without the prior use of antibiotics, and community-acquired CDIs are now thought to account for one quarter of infections [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Careful monitoring for C. difficile infection may include diagnostic testing of older patients with diarrhea who have recently been exposed to antibiotics and asking patients about recent hospital admissions and health care exposure. A 2018 Canadian analysis of isolates in community-acquired cases of C. difficile infection showed that all patients had been admitted in the previous year, 36 which indicates that many, and perhaps all, community-associated cases actually have nosocomial origins.…”
Section: Openmentioning
confidence: 99%